MODERNISASI PENDIDIKAN ISLAM (TELAAH PEMIKIRAN FAZLUR RAHMAN) - Moch Tohet (Universitas Nurul Jadid Paiton Probolinggo, East Java, 2019)
As a thinker was born in the early 20th century AD, Fazlur Rahman had lived at a time when science and technology had developed. According to him, the development of science and technology is felt to bring currents and impacts on education, especially Islamic education. In Fazlur Rahman's view, what must be done to renew Islamic education is to bring Islamic education to the right vision and mission, namely education that has the vision and mission of the Qur'an. Where the main vision and mission of the Qur'an is to